Time-resolved molecule counting by photon statistics across the visible spectrum - Grußmayer, Kristin Stefanie; Herten, Dirk-Peter (Physical chemistry, chemical physics, 2017)
In the past few years quantification of fluorescently labeled (bio-) molecules has become of increasing importance and several approaches have been developed to address this task. Counting by photon statistics measures the distribution of multiple photon detection events that carry information about the number and brightness of independently emitting fluorophores. The method enables absolute and non-destructive quantification, with the quality of estimates critically depending on the ability to accurately measure said photon statistics. Here, we present a combination of simulations and experiments that relate fundamental properties of fluorophores, i.e. their molecular brightness and photostability, to important experimental conditions, i.e. excitation power and acquisition time. Thereby, experimental settings and analysis parameters can be quantitatively evaluated, making counting by photon statistics a robust method for absolute counting of the number of emitters in a diffraction limited observation volume. We show that the time-resolution of counting varies with the fluorophore brightness and can be as fast as 10-100 ms. At the same time, the range of suitable fluorophores can be easily assessed. We evaluated the brightness and photostability of 16 organic dyes across the visible spectrum, providing information crucial for a range of single-molecule spectroscopy applications. This opens up exciting possibilities to analyze absolute stoichiometries in dynamic multi-component complexes.